Comprehensive assessment on the applications of oncolytic viruses for cancer immunotherapy - Omole, Richard Kolade; Oluwatola, Oluwaseyi; Akere, Millicent Tambari; Eniafe, Joseph; Agboluaje, Elizabeth Oladoyin; Daramola, Oluwafemi Bamidele; Ayantunji, Yemisi Juliet; Omotade, Temiloluwa Ifeoluwa; Torimiro, Nkem; Ayilara, Modupe Stella; Adeyemi, Oluwole Isaac; Salinsile, Olubusola Sajanat (Frontiers in Pharmacology, 2022)
The worldwide burden of cancers is increasing at a very high rate, including the aggressive and resistant forms of cancers. Certain levels of breakthrough have been achieved with the conventional treatment methods being used to treat different forms of cancers, but with some limitations. These limitations include hazardous side effects, destruction of non-tumor healthy cells that are rapidly dividing and developing, tumor resistance to anti-cancer drugs, damage to tissues and organs, and so on. However, oncolytic viruses have emerged as a worthwhile immunotherapeutic option for the treatment of different types of cancers. In this treatment approach, oncolytic viruses are being modeled to target cancer cells with optimum cytotoxicity and spare normal cells with optimal safety, without the oncolytic viruses themselves being killed by the host immune defense system. Oncolytic viral infection of the cancer cells are also being genetically manipulated (either by removal or addition of certain genes into the oncolytic virus genome) to make the tumor more visible and available for attack by the host immune cells. Hence, different variants of these viruses are being developed to optimize their antitumor effects. In this review, we examined how grave the burden of cancer is on a global level, particularly in sub-Saharan Africa, major conventional therapeutic approaches to the treatment of cancer and their individual drawbacks. We discussed the mechanisms of action employed by these oncolytic viruses and different viruses that have found their relevance in the fight against various forms of cancers. Some pre-clinical and clinical trials that involve oncolytic viruses in cancer management were reported. This review also examined the toxicity and safety concerns surrounding the adoption of oncolytic viro-immunotherapy for the treatment of cancers and the likely future directions for researchers and general audience who wants updated information.